ANALISIS KEDISIPLINAN DAN MOTIVASI DALAM MENINGKATKAN KUALITAS KERJA PEGAWAI(STUDI KASUS PADA DISTRIK TELUK KIMI, KABUPATEN NABIRE) - Kostantina Waray; Yoel Pasae; Agustinus Ba’ka (Paulus Journal of Accounting (PJA), 2024)
This study aims to analyze the role of discipline and motivation in improving employee work quality in Teluk Kimi District, Nabire Regency. Work discipline and motivation are key factors influencing productivity and the effectiveness of public services. This research employs a qualitative approach with a descriptive method, where data is collected through in-depth interviews, observations, and document studies. The findings indicate that employee discipline levels need improvement, particularly in adherence to work regulations and punctuality. The primary factors affecting discipline include lack of supervision, insufficient enforcement of sanctions, and challenging geographical conditions. Meanwhile, employee motivation is influenced by intrinsic factors such as job satisfaction and social responsibility, as well as extrinsic factors like financial incentives and recognition from leadership.